Violencia de género en los estudiantes de 3ro de BGU de la Unidad Educativa Capitán Edmundo Chiriboga - Barriga Valdiviezo, Henry Geovany (2020)
The objective of this research is to determine the presence of gender violence in the 3rd BGU students in “Captain Edmundo Chiriboga” Educational Unit. A topic of great importance, considering that gender violence in our social context is present, it affects the individual in the different spheres physically, psychologically, sexually and socially. It causes negative consequences such as low self-esteem, isolation, lack of concentration, low academic performance, lack of attention, among others. Methodologically, we worked with a quantitative approach and non-experimental design, basic type, in situ, at a descriptive level. The intentional non-probabilistic sample was composed by sixty students. The GENDER VIOLENCE TYPE AND PHASE EVALUATION SCALE (EETFVG) was applied. After the analysis and interpretation of the results, it is concluded that there is gender violence in students: physical violence (23.3%), psychological (6.7%), sexual (5%) and social (5%). Beliefs about gender-based violence revolve around: “I believe that I am able to carry out a life project in the future and alone” (63.3%); “I believe that aggression is not necessary” (73.3%); “I believe that what happens in a relationship is private and should not be told to anyone (20%).